A neurophysiological investigation of anticipation to pain in Parkinson's disease. (13th September 2019) - Martin, Sarah L.; Jones, Anthony K. P.; Brown, Christopher A.; Kobylecki, Christopher; Silverdale, Monty A.
Abstract: Chronic pain is common in people with Parkinson's disease and is often considered to be caused by the motor impairments associated with the disease. Altered top‐down processing of pain characterises several chronic pain conditions and occurs when the cortex modifies nociceptive processing in the brain and spinal cord. This contrasts with bottom‐up modulation of pain whereby nociceptive processing is modified on its way up to the brain. Although several studies have demonstrated altered bottom‐up pain processing in Parkinson's, the contribution of enhanced anticipation to pain and atypical top‐down processing of pain has not been fully explored. During the anticipation to noxious stimuli, EEG source localisation reported an increased activation in the midcingulate cortex and supplementary motor area in the Parkinson's disease group compared to the healthy control group during mid [−1, 500 –1, 000]‐and late anticipation [−500 0], indicating enhanced cortical activity before noxious stimulation. The Parkinson's disease group was also more sensitive to the laser and required a lower voltage level to induce pain. This study provides evidence supporting the hypothesis that enhanced top‐down processing of pain may contribute to the development of chronic pain in Parkinson's. Additional research to establish whether the altered anticipatory response is unique to noxious stimuli is required as no control stimulus was used within the current study. With further research to confirm these findings, our results inform a scientific rationale for novel treatment strategies of pain in Parkinson's disease, including mindfulness, cognitive therapies and other approaches targeted at improving top‐down processing of pain. Abstract : Parkinson's patients showed an increased activation in the midcingulate and supplementary motor area during the anticipation of noxious stimuli. The augmented anticipation was independent of motor impairment, chronic pain severity, mood and catastrophising behaviours. Therefore, demonstrating the high prevalence of chronic pain in Parkinson's may be caused by altered central pain processing.